2011
DOI: 10.1111/j.1365-3083.2011.02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter ‐817C>T Variant of B Lymphocyte Stimulator Gene (BLyS) and Susceptibility to Endometriosis‐Related Infertility and Idiopathic Infertility in Brazilian Population

Abstract: Many theories have been proposed to explain the development of endometriosis, and recently, autoimmune aetiology has been suggested. Besides, it is well known that endometriosis, especially the advanced disease, may impair fertility. B lymphocyte stimulator (BLyS) is a cytokine produced by macrophages and is necessary for normal B cell development. One of the most studied polymorphisms is the ‐817C/T in the promoter region of the gene. We aimed to assess the association between endometriosis‐related infertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…It was previously reported in the Brazilian population that polymorphisms in the nuclear factor-κB gene promoter, B lymphocyte stimulator gene promoter and TYK2 were associated with endometriosis-related infertility. 33, 34, 35 Nevertheless, we report here for the first time that in the Chinese Han population the CYP19 rs700518 AA genotype is associated with endometriosis-related infertility. This result indicates clinical relevance with regard to two aspects.…”
Section: Discussionmentioning
confidence: 61%
“…It was previously reported in the Brazilian population that polymorphisms in the nuclear factor-κB gene promoter, B lymphocyte stimulator gene promoter and TYK2 were associated with endometriosis-related infertility. 33, 34, 35 Nevertheless, we report here for the first time that in the Chinese Han population the CYP19 rs700518 AA genotype is associated with endometriosis-related infertility. This result indicates clinical relevance with regard to two aspects.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, Christofolini et al (2011) [126] performed a casecontrol study in 165 infertile women with endometriosis, 83 women with idiopathic infertility, and 145 fertile women; the results disclosed similar genotype and allelic frequencies between the endometriosis-related infertility and control group, regardless the disease stage. However, a statistically significant difference was observed regarding the idiopathic infertile group compared with controls.…”
Section: Blys-tumor Necrosis Factor (Ligand) Superfamily Member 13b mentioning
confidence: 56%
“…Once, in a study by Graaff et al (2010) [125], the genotype frequencies of patients with deep infiltrating endometriosis were not in Hardy-Weinberg equilibrium, and the authors did not mention the reproductive status of their patients. Christofolini et al (2011) [126] supposed that, maybe, in the Graaff et al sample, some patients presented with infertility associated with endometriosis. The authors concluded that BLyS Ϫ817C/T polymorphism may play a role in the pathogenesis of infertility in Brazilian population.…”
Section: Blys-tumor Necrosis Factor (Ligand) Superfamily Member 13b mentioning
confidence: 95%
“…Numerous studies have reported that the number of B cells increased in the PF of patients with endometriosis (144, 145). In contrast, some reports demonstrated that there is no significant difference in the B cells count of PF between endometriosis patients and patients in the control group (146). A few other studies have also demonstrated decreased numbers of B cells (147).…”
Section: B Lymphocytesmentioning
confidence: 94%